Monitoramento da interação e colaboração no ambiente Moodle: um estudo de caso - Mônego, Leomar Cassol (2019)
The use of Digital Information and Communication Technologies (TDIC) in the educational area points out new alternatives for learning, extending education beyond the face-to-face environment. The present study is based on a groupware scenario in the blended learning modality and was developed in the research line of Development of Networked Educational Technologies of the Graduate Program in Networked Educational Technologies of the Federal University of Santa Maria. The context created uses innovative methodologies supported by virtual environments and is part of the initial training of teachers of the Exact Sciences degree course (CLCE) of the Federal University of Pampa (UNIPAMPA) under the University-School Connections Program. The research aims to provide and evaluate the participation, interaction and collaboration of students and teachers in the proposed scenario. For this it was necessary to plan and implement specific activities / tools in the Virtual Teaching and Learning Environment (AVEA). This is a qualitative and quantitative research of the case study type, and to achieve this intent, we intend to use as an instrument of data collection questionnaires open and closed questions of participants and records of actions performed by users in AVEA. It was characterized with the results obtained that AVEA proved to be a platform of great collaborative potential, even though the teacher has a fundamental role in the careful choice of resources to promote this potential. Student follow-up analyzes used specific software that could be made available to teachers for their assessment practices, enabling them to better understand students' behavior and identify possible learning problems, allowing them to intervene when possible. A guide to the tools used, intended for teachers, was prepared as the final product of the dissertation. Finally, it is worth mentioning the intention to create a collaborative practice among the participants is emphasized so that they understand that problem solutions can be carried out collectively, thus modifying their ways of thinking and building their own knowledge.